Kształtowanie więzi organizacyjnych w strukturach sieciowych - Cabała, Paweł (Shaping Organizational Relations in Network Structures, 2005)
Article presents problem of organizational relations in network structures. At the beginning of the analysis only term "organizational relations" was subjected in context of the traditional and contemporaneous principles of establishing of the organizational structures. Next the division of network structures was proposed by using of two criterions: intensity and range of the organizational relations. Shaping of the organizational relations was based on conception of the chain value. Considerations focuses on problem of the cooperation and communication in the network structures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 36-42